Association of Plaque Composition and Vessel Remodeling in Atherosclerotic Renal Artery Stenosis: A Comparison With Coronary Artery Disease - Kataoka, Tetsuro (2009)
OBJECTIVES: The current study was designed to investigate the relationship between renal arterial structure and vessel remodeling in patients with atherosclerotic renal artery stenosis (RAS), compared with that seen in coronary artery disease (CAD). BACKGROUND: The nature and the tissue characterization of atherosclerotic RAS lesions have not been fully explored. METHODS: Gray scale and virtual histology (VH) intravascular ultrasound imaging was used to assess 23 lesions in 14 consecutive RAS patients and 20 left main trunk lesions in age-matched CAD patients. Analysis included assessment of vessel area and atherosclerotic plaque area of the main renal artery or left main trunk. Plaque was characterized as fibrous tissue, fibro-fatty tissue, necrotic core, and dense calcium. Remodeling was assessed by means of the remodeling index (RI). RESULTS: Positive remodeling (defined as RI ≥1.05) was present in 15 RAS and 9 CAD lesions, whereas intermediate/negative remodeling (RI <1.05) was present in 8 RAS and 11 CAD lesions. VH showed that the fibrous tissue was the most prominent plaque composition, followed by fibro-fatty, necrotic core, and dense calcium in both vascular beds. Greater vascular adaptive enlargement was observed in slices with plaque burden ≤40% compared with plaque burden >40% (p < 0.001 for all). Vessel area had a positive association with the area of all VH components (p < 0.001, for all). VH analysis shows that the most powerful determinant of adaptive vessel enlargement is dense calcium in RAS (p < 0.001), while that is necrotic core in CAD (p < 0.001). Necrotic core and dense calcium areas were greater in lesions with positive remodeling compared with intermediate/negative remodeling (p = 0.03, p = 0.03, respectively, in RAS; p = 0.005, p = 0.03, respectively, in CAD). CONCLUSIONS: The current study demonstrates in humans that plaque composition as assessed by VH intravascular ultrasound has an important role of adaptive vessel enlargement, and it is related to renal artery remodeling in RAS in a pattern similar to CAD.